The Candida albicans Hwp2 is necessary for proper adhesion, biofilm formation and oxidative stress tolerance - Younes, Samer; Bahnan, Wael; Dimassi, Hani I.; Khalaf, Roy A. (Microbiological research, 2011)
Candida albicans is an important fungal pathogen of humans that is responsible for the majority of mucosal and systemic candidiasis. The host–pathogen interaction in C. albicans has been the subject of intense investigation as it is the primary step that leads to establishment of infection. Hwp2 is a cell wall GPI-anchored cell wall protein that was previously shown to be necessary for hyphal and invasive growth on solid media. The purpose of the current study is to further characterize the protein as far as its role in oxidative stress, sensitivity to cell wall disrupting agents, adhesion to human epithelial and endothelial cells, biofilm formation and chitin content. It appears that Hwp2 is necessary for proper oxidative stress tolerance, adhesion and biofilm formation as an hwp2 null is more susceptible to increasing doses of hydrogen peroxide, unable to adhere efficiently to epithelial and endothelial cell lines and unable to form wild type biofilm levels.